Psychological Stress among University Students in Pakistan Due to COVID -19 Pandemic and Social Distancing: A Study of Social and Familial Factors Affecting Stress Levels - Zubair, Faiza; Akmal, Asma; Laeeque, Bisma (Nurture, 2022)
Purpose: At present, the world is in the grip of COVID-19, a new health threat that has been declared a pandemic. To reduce the number of COVID-19 cases, preventive measures such as lockdowns and social distancing have been adopted. This situation is a cause of psychological stress for humans, especially among the youth. This study was conducted to analyze the stress levels of university students and the factors that contributed to reduction in stress levels. Methodology: A sample of 997 students was taken from the University of Home Economics Lahore. The data was collected through a detailed online survey and presented graphically with the help of tables and graphs. The impact of family size, family setup, and house size, the presence of kids and pets at home as well as religious following on stress levels was studied using chi-square tests and tests of correlation. Findings: Significant correlations were found supporting the idea that all of the aforementioned factors played a significant role in reducing stress levels among the young students. Practical implications: This research will help the educators and psychologists tackle students’ stress issues during social distancing. This research is an addition to the existing literature developed during COVID-19.